Craving Behavior Intervention in Ameliorating College Students' Internet Game Disorder: A Longitudinal Study - Deng, Lin-Yuan; Liu, Lu; Xia, Cui-Cui; Lan, Jing; Zhang, Jin-Tao; Fang, Xiao-Yi (Frontiers in Psychology, 2017)
Craving, as a central feature of addiction and a precursor of relapse, is targeted recently in addiction intervention. While Internet gaming disorder (IGD), conceptualized as a behavioral addiction, is lack of effective treatment practice and exploration of its mechanism. This research aims to test the effectiveness and detect the active ingredients of craving behavior intervention (CBI) in mitigation of IGD among young adults. A total of 63 male college students with IGD were assigned into the intervention group (six-session CBI intervention) or the waiting-list control group. Structured questionnaires were administered at pre-intervention (T1), post-intervention (T2), three-month follow-up (T3) and six-month follow-up (T4). Compared to the control group, a significant decrease in the severity of IGD in intervention group was found at post-intervention and lasting to six months after intervention. The value changes of craving could partially mediate the relationship between intervention and changes of IGD among all effects tests (immediate, T2-T1; short-term, T3-T1; and long-term effects, T4-T1). Further explorations of the active ingredients of intervention found depression relief and shift of psychological needs from Internet to real life significantly predict craving amelioration at both post-intervention and 6-month follow-up. Although preliminary, the current study provides evidence for the value of craving-aimed intervention practice in IGD treatment and identifies two potential active ingredients for mitigation of craving, and the long-term therapeutic benefits are further conferred. Registry name: The behavioral and brain mechanism of IGD; URL: https://www.clinicaltrials.gov/ct2/show/NCT02550405; Registration number: NCT02550405.